2011
DOI: 10.1021/jm201129m
|View full text |Cite|
|
Sign up to set email alerts
|

Fragment-Based Discovery of Indole Inhibitors of Matrix Metalloproteinase-13

Abstract: Matrix metalloproteases (MMPs) play an important role in cartilage homeostasis under both normal and inflamed disease states and, thus, have become attractive targets for the treatment of arthritic diseases. Herein, we describe the identification of a potent, selective MMP-13 inhibitor, developed using fragment-based structure-guided lead identification and optimization techniques. Virtual screening methods identified a novel, indole-based MMP-13 inhibitor that bound into the S1' pocket of the protein exhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 35 publications
0
41
0
Order By: Relevance
“…7 Non zinc-chelating inhibitors have been reported for MMP-8, 85 MMP-12 [86][87][88] and MMP-13 [89][90][91][92][93][94][95][96][97][98][99] . The enthusiasm for non zinc-chelating inhibitors started with the discovery of compound 29 at Sanofi laboratories.…”
Section: Positive Impactmentioning
confidence: 99%
“…7 Non zinc-chelating inhibitors have been reported for MMP-8, 85 MMP-12 [86][87][88] and MMP-13 [89][90][91][92][93][94][95][96][97][98][99] . The enthusiasm for non zinc-chelating inhibitors started with the discovery of compound 29 at Sanofi laboratories.…”
Section: Positive Impactmentioning
confidence: 99%
“…We cannot cover all of these studies and a number of recently published reviews can be consulted [10,13,15,21,101,102]. Recent studies that utilized fragment growing as an optimization strategy include the discovery of Beta-site amyloid precursor protein cleaving enzyme 1 (BACE1) [70], Acetylcholine-binding protein (AChBP) [103], Matrix metalloproteinases (MMPs) [104] and phosphatidylinositol-3 kinases (PI3Ks) [88] inhibitors. In one of these studies, Cheng et al [70] screened a library of 4000 fragments against BACE1, using SPR and identified 2-aminoquinoline as initial fragment hit.…”
Section: Fragment Growingmentioning
confidence: 99%
“…An overview of some of the recent successes is presented in ( Table 3) that includes work by Taylor et al [104] who carried out virtual screening of an in-house library to identify fragment hits that can bind S1' pocket of MMP-13, a member of MMPs with apparent role in rheumatoid arthritis. The high scoring hits from virtual screening were enriched with some diverse scaffolds to prepare a library of approximately 1000 fragments that was further characterized using biochemical screening, STD NMR, size exclusion chromatography and mass spectrometry.…”
Section: Recent Success In Computational Fragment Screeningmentioning
confidence: 99%
“…We have found only some rare examples of cross-coupling reactions involving indoles bearing an electron-withdrawing ester group in the 2-position, which indicates that this process has hardly been studied. [17] In the case of model compound 7b, the amide fragment could also be the reason for an additional problem with the reactivity resulting from coordination of a transition metal at this site. Therefore, we decided to investigate this reaction more thoroughly, and screened various catalytic systems {Pd(PPh 3 ) 4 , Pd(dppf) 2 Cl 2 , Pd(dba) 2 + PtBu 3 , Pd(dba) 2 + BINAP, Pd(dba) 2 + Xantphos [dppf = 1,1Ј-bis(diphenylphosphino)ferrocene; dba = dibenzylideneacetone; BINAP = 2,2Ј-bis(diphenylphosphino)-1,1Ј-binaphthyl; Xantphos = 4,5-bis(diphenylphosphino)-9,9-dimethylxanthene]} in the presence of bases (Na 2 CO 3 , K 3 PO 4 ) for the reaction with phenyl boronic acid in various solvents (dioxane/H 2 O, toluene).…”
Section: Introductionmentioning
confidence: 99%